1969
DOI: 10.1152/ajplegacy.1969.217.4.974
|View full text |Cite
|
Sign up to set email alerts
|

Transport of neutral amino acids from feline cerebrospinal fluid

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1970
1970
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…have been discussed previously (Ashcroft, Dow & Moir, 1968;Ashcroft, Crawford, Dow & Moir, 1969 Cutler & Lorenzo (1968) and Snodgrass, Cutler, Song Kang & Lorenzo (1969) found that the clearances of other amino acids from c.s.f. also involve saturable carrier-mediated systems.…”
Section: Discussionmentioning
confidence: 75%
“…have been discussed previously (Ashcroft, Dow & Moir, 1968;Ashcroft, Crawford, Dow & Moir, 1969 Cutler & Lorenzo (1968) and Snodgrass, Cutler, Song Kang & Lorenzo (1969) found that the clearances of other amino acids from c.s.f. also involve saturable carrier-mediated systems.…”
Section: Discussionmentioning
confidence: 75%
“…Overlapping between systems exists when most amino acids are transported by more than one system (Cohen and Lajtha, 1972). The difference existing between the free amino acid levels in plasma and CNS can be the consequence of restriction into the CNS from blood, rapid exit from the CNS by active process, rapid metabolic utilization, or a combination of the above (Bito et al, 1966;Levin et al, 1966a and b;Snodgrass et al, 1969). On the other hand, it was claimed that amino acids are transported from CSF to blood through the brain (Snodgrass et al, 1969) and that influx and/or efflux are affected by drugs and analogues of amino acids in different ways (Gaull et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Influx and efflux of amino acids from the brain occurs by specific mechanisms. Such mechanisms might also serve to regulate the brain amino acid concentration (Snodgrass et al, 1969).…”
mentioning
confidence: 99%
“…There is recent evidence that a wide range of amino acids is transported by a carrier mediated process across the blood-brain (cerebral capillary endothelium) and blood-cerebrospinal fluid (choroid plexus) barriers (Betz, Gilboe, and Drewes, 1975;Lajtha, 1974;Oldendorf, 1971;Snodgrass, Cutler, Kang, and Lorenzo, 1969). In the case of glycine, there is experimental evidence that this neutral amino acid is actively transported into brain slices (Lajtha and Toth, 1963), in uitro and in uiuo choroid plexus (Caruthers and Lorenzo, 1974;Coben, Cotlier, Beaty, and Becker, 1971).…”
Section: Introductionmentioning
confidence: 99%